Risk management strategies and probabilistic failure pressure model development for pipelines with crack-like defect - ICASP14; Kere, Kiswendsida; Huang, Qindan (My University, 2023)
Optimal inspection and maintenance planning for deteriorating pipelines is necessary for cost-effective risk management decisions. The objective of this study is to develop a framework for determining the optimal inspection and maintenance planning for deteriorating pipelines considering failure probabilities. The framework is developed based on a decision tree model by using analytical methods to evaluate events and considers the inspection schedules and the threshold for repair as the design variables. To evaluate the probability of failure, an accurate probabilistic failure pressure model for thin-walled pipelines containing crack-like defects is proposed. The failure pressure prediction model is developed by adding a correction factor to the modified Ln-Secant method, a semi-empirical model developed previously. It is found that the proposed model provides unbiased and more accurate predictions. To illustrate the proposed framework, a simple problem of a steel pipeline with an initial crack is used, where a stochastic model of crack propagation is assumed. The case study indicates that finding an optimal inspection and maintenance planning is a compromise of the costs of inspection, repair, and failure.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED